Residential wire codes: reproducibility and relation with measured magnetic fields. Issue 5 (May 1998) - Tarone, R E; Kaune, W T; Linet, M S; Hatch, E E; Kleinerman, R A; Robison, L L; Boice, J D; Wacholder, S
Abstract : OBJECTIVES: To investigate the reproducibility of wire codes to characterise residential power line configurations and to determine the extent to which wire codes provide a proxy measure of residential magnetic field strength in a case-control study of childhood leukaemia conducted in nine states within the United States. METHODS: Misclassification of wire codes was assessed with independent measurements by two technicians for 187 residences. The association between categories of wire code and measured level of magnetic field was evaluated in 858 residences with both a wire code measurement and a 24 hour measurement of the magnetic field in the bedroom. The strength of the association between category of wire code and risk of leukaemia was examined in two regions with different average levels of magnetic field in homes with high categories of wire code. RESULTS: The reproducibility of any of three different classifications of wire codes was excellent (kappa > or = 0.89). Mean and median magnetic fields, and the percentage of homes with high magnetic fields increased with increasing category for each of the wire code classification schemes. The size of the odds ratios for risk of leukaemia and high categories of wire code did not reflect the mean levels of the magnetic field in those categories in two study regions. CONCLUSION: Misclassification of categories of wire code is not a major source of bias in the study. Wire codes provide a proxy measure of exposure to residential magnetic fields. If magnetic fields were a risk factor for leukaemia, however, there would be some attenuation of risk estimates based on wire codes because of misclassification of exposure to magnetic fields at both extremes of the wire code range. The lack of an association between high categories of wire code and risk of leukaemia cannot be explained by a failure of the wire code classification schemes to estimate exposure to magnetic fields in the study area.